2014
DOI: 10.2135/cropsci2013.09.0625
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mapping of Stripe Rust Resistance in Hard Red Winter Wheat TAM 111 Adapted to the U.S. High Plains

Abstract: Stripe rust, also known as yellow rust, caused by Puccinia striiformis Westend. f. sp. tritici Erikss. (Pst), is one of the most important foliar diseases of wheat (Triticum aestivum L.) in the United States and other parts of the world. To investigate the genetic basis of resistance conferred by the winter wheat cultivar ‘TAM 111’, a mapping population of 124 F5 and F6 derived recombinant inbred lines (RILs) developed from the cross of ‘TAM 112’/TAM 111 was evaluated against Pst populations in eight environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 58 publications
2
46
0
Order By: Relevance
“…The number of the environment-specific minor QTL for quantitative stripe rust resistance identified in the current study with high-resolution maps is higher than the ones identified by Basnet et al (2014). In addition to the major QTL on chromosome 2B, seven minor QTL on chromosomes 1A, 2A, 4A, 4B, 6B, and 7D were identified, which confirmed those five QTL identified by Basnet et al (2014), and the other two were novel.…”
Section: Genetic Basis Of Stripe Rust Resistancesupporting
confidence: 81%
See 4 more Smart Citations
“…The number of the environment-specific minor QTL for quantitative stripe rust resistance identified in the current study with high-resolution maps is higher than the ones identified by Basnet et al (2014). In addition to the major QTL on chromosome 2B, seven minor QTL on chromosomes 1A, 2A, 4A, 4B, 6B, and 7D were identified, which confirmed those five QTL identified by Basnet et al (2014), and the other two were novel.…”
Section: Genetic Basis Of Stripe Rust Resistancesupporting
confidence: 81%
“…The major QTL on the long arm of chromosome 2B, previously designated as QYr.tam-2BL (Basnet et al, 2014;Fig. 1A), was the most important resistance loci identified in TAM 111 in the current study.…”
Section: Genetic Basis Of Stripe Rust Resistancementioning
confidence: 50%
See 3 more Smart Citations